Science and Technology Section's General Discussion Group: Highlights from Midwinter 2000 - Kimberly A. Lyons-Mitchell; Julia A. Zimmerman (Issues in Science and Technology Librarianship, 2000)
The article summarizes the Science and Technology Section's General Discussion Group from ALA Midwinter 2000.